1999
DOI: 10.1038/sj.bjc.6690656
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with irinotecan and cisplatin as neoadjuvant chemotherapy in locally advanced cervical cancer

Abstract: ) given intravenously on day 1. Treatment was repeated every 4 weeks for a total of two or three cycles. Among 23 eligible patients (median age: 59 years), three showed complete response (13%), 15 showed partial response (65%), for an overall response rate of 78% (95% confidence interval 58-90%). Stable disease was observed in four cases (17%) and progressive disease in one (4%). The median time to failure and median survival time have not yet been reached. Of the 52 treatment cycles administered, diarrhoea an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Table 5 shows the results of the present study in comparison to those of previous reports (Sugiyama et al, 1999;Hwang et al, 2001;Dueñas-Gonzalez et al, 2001;D'Agostino et al, 2002;Di Vagno et al, 2003;Dueñas-Gonzalez et al, 2003;Umesaki et al, 2004; and this study. Table 5.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Table 5 shows the results of the present study in comparison to those of previous reports (Sugiyama et al, 1999;Hwang et al, 2001;Dueñas-Gonzalez et al, 2001;D'Agostino et al, 2002;Di Vagno et al, 2003;Dueñas-Gonzalez et al, 2003;Umesaki et al, 2004; and this study. Table 5.…”
Section: Discussionsupporting
confidence: 65%
“…This analysis suggested the effectiveness of NAC, if: one cycle of treatment lasted no more than 14 days; and the DI of CDDP exceeded 25 mg/m 2 /week (Neoadjuvant Chemotherapy for Cervical Cancer Metaanalysis Collaboration., 2003). Sugiyama et al reported a CDDP/CPT-11 therapy schedule involving CPT-11 doses on Days 1, 8, and 15 (one course = 28 days) (Sugiyama et al, 1999). We evaluated the efficacy and safety of CDDP/CPT-11 therapy, reportedly an effective NAC regimen, using modified doses and administration schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugiyama et al (5,6) reported that patients with cervical carcinoma treated with CPT-11 (60 mg/m 2 ) on days 1, 8 and 15 and CDDP (60 mg/m 2 ) on day 1 showed response rates of 59% for advanced/recurrent carcinoma and 78% in NAC for locally advanced cervical carcinoma. In their study, however, treatment with CPT-11 on days 8 and 15 had to be skipped in a high percentage (31%) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a late phase II study in patients with cervical carcinoma, it exhibited relatively high efficacy, with a response rate of 23% (4). Sugiyama et al (5) reported that administration of CPT-11 (60 mg/m 2 ) on days 1, 8 and 15 with CDDP (60 mg/m 2 ) on day 1 yielded a response rate of 59% in cases of advanced or recurrent cervical cancer and 78% in cases in which this regimen was applied as a neoadjuvant chemotherapy for advanced cervical carcinoma (6).…”
Section: Introductionmentioning
confidence: 99%